Biochemical Impedance on Intracellular Functions of Vitamin B12 in Chronic Toxigenic Mold Exposures - Anyanwu, Ebere C. (ScientificWorldJournal, 2007)
A majority of patients with neurological disorders with chronic exposures to toxigenic molds and mycotoxins has vitamin B12 deficiency that is unrelated to dietary insufficiency. Vitamin B12 is a source of coenzymes, and participates in intracellular recycling of methionine, and in methionine synthase reactions. The biochemical processes that lead to B12 depletion and deficiency are not fully understood. This paper examines and assesses various most likely biochemical reasons that could impede upon the normal intracellular functions of vitamin B12 that lead to neurological manifestations. By biochemical implications and derivations, it is most likely that mycotoxins interrupt the structure and function of vitamin B12 through reactive interference with the normal One-Carbon metabolism leading to the observed clinical neurological manifestations such as nerve damage and, demyelination, degeneration of PNS leading to paralysis, progressive peripheral neuropathy, and spinal degeneration.